2016
DOI: 10.5620/eht.e2016022
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of the association between mobile phone use and symptoms of ill health

Abstract: ObjectivesThis study analyzed the associations between mobile phone call frequency and duration with non-specific symptoms.MethodsThis study was conducted with a population group including 532 non-patient adults established by the Korean Genome and Epidemiology Study. The pattern of phone call using a mobile phone was investigated through face-to-face interview. Structured methods applied to quantitatively assess health effects are Headache Impact Test-6 (HIT-6), Psychosocial Well-being Index-Short Form, Beck … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…We did not find any research article that explains how social patterns change with depression, but the review article by Baker et al [27] on online social networks suggests a complex relation involving factors that mediate or moderate the correlation and increase the variability in the findings. Furthermore, Cho et al [44] found a direct opposite correlation between genders (male negative, female positive) in the call duration and call frequency features. This suggests that social-based features should be treated as a highly personalized feature that should be assessed in a within-subject analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not find any research article that explains how social patterns change with depression, but the review article by Baker et al [27] on online social networks suggests a complex relation involving factors that mediate or moderate the correlation and increase the variability in the findings. Furthermore, Cho et al [44] found a direct opposite correlation between genders (male negative, female positive) in the call duration and call frequency features. This suggests that social-based features should be treated as a highly personalized feature that should be assessed in a within-subject analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-cultural study with people from Switzerland and Turkey, Hernández et al [29] found different correlation directions between the two groups in screen active frequency and number of running apps . Furthermore, several device-based features such as browser app usage and reading app usage have different correlation directions between genders (male positive, female negative) [33], and the two social features call duration and call frequency also exhibit different correlation directions between genders (male negative, female positive) [44]. …”
Section: Discussionmentioning
confidence: 99%
“…In a cross-cultural study with people from Switzerland and Turkey, Hernández et al [31] found different correlation directions between the two groups in screen active frequency and number of running apps. Furthermore, several device-based features such as browser app usage and reading app usage have different correlation directions between genders (male positive, female negative) [35], and the two social features call duration and call frequency also exhibit different correlation directions between genders (male negative, female positive) [45]. Transition time is currently only investigated by the research group of Saeb et al [7,51] where they did a study to replicate previous findings of the same features.…”
Section: Secondary Featuresmentioning
confidence: 70%
“…Faurholt-Jepsen et al [6] presented a new feature; missed calls which is statistically significantly correlated with the HDRS-17 (β = 0.05, p = .006). The result was presented in 2016, but not replicated in any of the later studies such as the comprehensive study on phone records with 532 subjects [45].…”
Section: Mood Assessmentmentioning
confidence: 91%
See 1 more Smart Citation